2019
DOI: 10.1523/jneurosci.1826-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Receptor Trafficking and Protein Synthesis Mediate the Facilitation of LTP by Secreted Amyloid Precursor Protein-Alpha

Abstract: Secreted amyloid precursor protein-alpha (sAPP␣) has growth factor-like properties and can modulate long-term potentiation (LTP) and memory. Here, we demonstrate that exposure to sAPP␣ converts short-lasting LTP into protein-synthesis-dependent late LTP in hippocampal slices from male rats. sAPP␤ had no discernable effect. We hypothesized that sAPP␣ facilitated LTP via regulated glutamate receptor trafficking and de novo protein synthesis. We found using a linear mixed model that sAPP␣ stimulated trafficking o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(63 citation statements)
references
References 64 publications
(122 reference statements)
4
59
0
Order By: Relevance
“…Notably, this up-regulation of mRNA translation was blocked 6 hours post activation by prior application of GluR antagonists, consistent with reports of GluRdependent LTP(65)(66)(67). These results were further corroborated by immunocytochemical SUnSET.Examining sub-cellular compartments through the unique benefits of tRNA-FRET, we determined that somatic and dendritic protein synthesis equally contributed to the pulsatile pattern of mRNA translation up-regulation, consistent with previous observations(110), and further strengthened by our presentation of the constant ratio of ~1 between somatic and dendritic mRNA translation levels regardless of cLTP induction and GluR inhibition.Research regarding tRNA itself, which has been limited for a long time, has recently attracted renewed attention. Aside from its canonical role as the adaptor that facilitates mRNA translation to proteins, tRNA participates in many additional cellular pathways, including N-terminal conjugation of amino acids to proteins, signal transduction pathways that respond to nutrient deprivation, and regulation of apoptosis (16, 19, 27).…”
supporting
confidence: 91%
“…Notably, this up-regulation of mRNA translation was blocked 6 hours post activation by prior application of GluR antagonists, consistent with reports of GluRdependent LTP(65)(66)(67). These results were further corroborated by immunocytochemical SUnSET.Examining sub-cellular compartments through the unique benefits of tRNA-FRET, we determined that somatic and dendritic protein synthesis equally contributed to the pulsatile pattern of mRNA translation up-regulation, consistent with previous observations(110), and further strengthened by our presentation of the constant ratio of ~1 between somatic and dendritic mRNA translation levels regardless of cLTP induction and GluR inhibition.Research regarding tRNA itself, which has been limited for a long time, has recently attracted renewed attention. Aside from its canonical role as the adaptor that facilitates mRNA translation to proteins, tRNA participates in many additional cellular pathways, including N-terminal conjugation of amino acids to proteins, signal transduction pathways that respond to nutrient deprivation, and regulation of apoptosis (16, 19, 27).…”
supporting
confidence: 91%
“…Despite many studies, the cell surface receptor(s) which transduce the sAPPα signal are yet to be conclusively identified, though specific candidates have emerged (Rice et al, 2017, 2019; Richter et al, 2018; Mockett et al, 2019). Here, we pharmacologically inhibited likely candidates mediating sAPPα’s plasticity-promoting effects and observed the effect on sAPPα-induced Arc protein levels (Figure 8).…”
Section: Resultsmentioning
confidence: 99%
“…Further, sAPPα is able to facilitate long-term potentiation (LTP; Taylor et al, 2008; Moreno et al, 2015), stimulate neurite outgrowth (Clarris et al, 1994), and regulate spine morphology (Hick et al, 2015). Recently, it has been shown that the molecular mechanisms underpinning these actions include enhancement of glutamate receptor trafficking, synaptodendritic protein synthesis and new gene transcription (Claasen et al, 2009; Chasseigneaux et al, 2011; Ryan et al, 2013; Mockett et al, 2019), yet these and other mechanisms have not been fully explored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aβ is well known for causing pathological dysregulation of postsynaptic trafficking of both the AMPA [39] and N -Methyl- d -aspartate (NMDA) [40]-type glutamate receptors. Notably, APP also has physiological roles in the function and trafficking of these glutamate receptors [41,42,43] and may thus be important for synaptic plasticity and learning/memory [44,45,46,47,48]. The actions of APP at the synapse are also known to be mediated by the secreted (s)APPs, mainly sAPPα generated by α-secretase cleavage [49,50,51,52,53].…”
Section: Introductionmentioning
confidence: 99%